Correlation between sputtering method, microstructure and properties of TiOx thin films deposited by reactive direct-current and high-power impulse magnetron sputtering - Lablali, Younes; Oubaki, Rachid; Ghailane, Anas; Alami, Jones; Makha, Mohammed (Thin solid films, 2024)
•TiOx films were deposited by magnetron sputtering at various oxygen flow fractions.•Microstructure, morphology and grain size of TiOx are affected by deposition method.•Correlation between phase constitution and particle energy distribution was studied. In this study, Titanium oxide (TiOx) thin films were produced via reactive High-Power Impulse Magnetron Sputtering (HiPIMS) and reactive Direct-current Magnetron Sputtering (DcMS). The influence of oxygen reactive gas content on the structural, morphological, and optical characteristics of TiOx films was analyzed using various techniques including X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, and UV–visible spectroscopy. We found that HiPIMS-deposited films exhibited a mixed anatase and rutile phase structure, while DcMS-deposited films showed a pure anatase structure. Additionally, HiPIMS deposited films demonstrated smaller grain sizes and smoother surfaces compared to DcMS deposited films. Elemental analysis revealed that HiPIMS-grown films were consistently over-stoichiometric, whereas a transition from sub to over-stoichiometric composition was observed in the DcMS-grown films. Moreover, the optical band gap values of TiOx films deposited via HiPIMS were higher than those deposited via DcMS, decreasing as the oxygen flow rate increased. TRIM calculations were employed to assess the average energy of particles reaching the growing film in both HiPIMS and DcMS depositions, confirming the observed structural differences.